Asymtomatic Angiomyolipoma of the Right Adrenal Gland - Monowarul, I; Amanullah, ATM; Alam, AKMK (Journal of Surgical Sciences, 2013)
Angiomyolipoma are commonly found in Kidney but extrarenal sites are also mentioned. It arising in adrenal is very rare entity, usually asymptomatic, diagnosed incidentally on radiological investigation of abdomen for other conditions. We report our experience with a 37-year-old man who presented with sudden feeling of jerking discomfort and generalized weakness. An USS showed adrenal mass, computerised tomography (CT) scan confirmed and outlined the adrenal mass.Adrenalectomy was performed and the histopathological features confirmed the diagnosis of adrenal angiomyolipoma. The patient recovered without any complications following surgery. DOI: http://dx.doi.org/10.3329/jss.v16i1.14449 Journal of Surgical Sciences (2012) Vol. 16 (1) : 47-48